2014
DOI: 10.3389/fpsyg.2014.00966
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved trauma in mothers: intergenerational effects and the role of reorganization

Abstract: A mother's unresolved trauma may interfere with her ability to sensitively respond to her infant, thus affecting the development of attachment in her own child, and potentially contributing to the intergenerational transmission of trauma. One novel construct within the Dynamic Maturational Model of Attachment and Adaptation (DMM) coding of the Adult Attachment Interview (AAI) is “reorganization,” a process whereby speakers are actively changing their understanding of past and present experiences and moving tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 40 publications
1
41
0
2
Order By: Relevance
“…It is important to note that despite significant evidence of the transmission of attachment styles across generations (both traumatic and nontraumatic), this transmission pathway may not always occur (Iyengar, Kim, Martinez, Fonagy, & Strathearn, ). Individuals can reorganise their attachments using a variety of methods via external and internally driven processes, as well as develop sustained relational security through resilience (Iyengar et al, ). Fostering and supporting these mechanisms may result in altering the transmission of attachment patterns and trauma across generations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that despite significant evidence of the transmission of attachment styles across generations (both traumatic and nontraumatic), this transmission pathway may not always occur (Iyengar, Kim, Martinez, Fonagy, & Strathearn, ). Individuals can reorganise their attachments using a variety of methods via external and internally driven processes, as well as develop sustained relational security through resilience (Iyengar et al, ). Fostering and supporting these mechanisms may result in altering the transmission of attachment patterns and trauma across generations.…”
Section: Resultsmentioning
confidence: 99%
“…Developmental neuroplasticity is such that while early life experiences are mapped onto the structure and functioning of the brain, infant brains can also rebound from traumatic experiences, particularly if they experience stable, nurturing caregiving (Harden et al, ). While attachment is formed in early relationships, it is also influenced by later relationships or circumstances (Bowlby, ; Iyengar et al, ) and can be effectively “reorganised.” The reorganisation of attachment prior to parenting may result in significant alterations to the transmission of trauma through attachment relationships (Iyengar et al, ). This may occur during trauma therapy, but it also forms another potential component prevention approaches not explored here.…”
Section: Discussionmentioning
confidence: 99%
“…Additional modifiers included intrusions of forbidden negative affect (i.e., sudden disinhibition of extreme inhibition of fear, anger, or desire for comfort attachment behavior) and expressed somatic signs (i.e., somatic states that disrupt strategic behavior). The DMM also identifies strategies that are in the process of change (i.e., reorganizing; Iyengar, Kim, Martinez, Fonagy, & Strathearn, ). If reorganizing markers in DMM attachment assessments, identified by clinicians and validated on a case‐by‐case basis, can be empirically validated in larger comparative studies, it will represent a significant advance for intervention research that has had only modest success in shifting insecure attachment (Bakermans‐Kranenburg, van IJzendoorn, & Juffer, , ; Mountain, Cahill, & Thorpe, ).…”
Section: Point 2: the Abc+dmm May Be Better Attuned To The Issues Of mentioning
confidence: 99%
“…Profound early deprivation, as was seen in Romanian institutional rearing, has been observed to lead to severe long‐term attachment disturbances and social deficits . The developmental literature is replete with decades of prospective longitudinal and cross‐sectional studies linking early trauma and/or disrupted attachment to long‐term social and attachment dysfunctions . There has been an increasing number of studies linking these social deficits to compromised OT functions …”
Section: Oxytocin Systemmentioning
confidence: 99%
“…89,90 The developmental literature is replete with decades of prospective longitudinal and cross-sectional studies linking early trauma and/or disrupted attachment to long-term social and attachment dysfunctions. [91][92][93][94] There has been an increasing number of studies linking these social deficits to compromised OT functions. 57,95,96 Recent advances in neuroscience have revealed that there may be a significant overlap in the neurobiological mechanisms that underpin social attachment and addiction.…”
Section: Behavioral Levelmentioning
confidence: 99%